Escola Brasileira de Trombone: um estudo sobre práticas pedagógicas - Reis, Marciley da Silva (2016)
This master thesis deals with educational processes in music related to the trombone in Brazil through the identification, selection and analysis of pedagogical practices, as well as the evidence and the formation process of the Brazilian Trombone School. The theoretical contribution is supported by Leão (2013) - music research methodology, Freire (2011), Tardif (2000 and 2002) and Gauthier (2013) - education - Shigunov Neto & Maciel (2008) and Amorim (2012) - society and culture -, as well as other works that focus on and discuss the musical and trombonistic knowledge and practices, such as Santos (1999 and 2016), Gagnard (1974), Kemp (1995) and Costa (1999). Within an interpretive perspective of research, the philosophical approach used was hermeneutics, combined with the qualitative paradigm, also using quantitative resources. In addition, the research had a descriptive and historical character, pointing to educational experiences through interviews and data in order to systematize the teaching-learning approaches of the Brazilian trombone aspect. In order to answer questions about the Brazilian Trombone School and its artistic- instrumental construction processes in relation to teaching and learning, the research was conducted in two stages: bibliographical survey and field research. This fact was justified by the fact that, up to the present moment, there is still no systematization of this process, nor cataloging of documents referring to its description, and, as such, of the pedagogical practices employed. It was believed that this systematization could contribute positively to the didactic- methodological orientation, being able to suggest resolutions for possible pedagogical problems. The methodological process of this research was based on bibliographic review and data collection. Thus, data obtained from oral sources (10 Brazilian trombonist teachers interviewed), theoretically based, served to discuss the teaching-learning process of the trombone. For the empirical analysis, for the application of the questionnaires, renowned trombonist teachers of recognized trombone study centers in Brazil were selected and interviewed, for which the same questionnaire was applied in a semi-open format, with a pre-elaborated script of Questions that specially questioned about the specificities of the musical experience, the knowledge about the study in Brazil and its pedagogical practices. This research was validated (ensuring confidentiality and reliability - in addition to legal and moral protection of the researched and the researcher) of the Informed Consent Term - TCLE (in compliance with the legal terms and the Ethics Committee - CEP). This dissertation is justified by the social relevance of the theme for music education and contemporary society at this time of changes in the public educational policies that reach the teaching of music in Brazil. Through the verification of all content, it was possible to conclude on the existence of the Brazilian Trombone School and its level of development, as well as on the methods, methodologies, strategies, and participants that act in the implementation of the same. It is estimated that the results of the final product can contribute to the advancement of knowledge in the area of music and education, and to the affirmation/strengthening of the Brazilian Trombone School.